Content Factors Of The Formation Of Moral Characters In Primary Class Students - Aziza Maxamatdjonovna Mamatova (Academia One Publishing, 2023)
the article discusses the content of the formation of moral qualities in primary school students
Keywords: ethics; virtue; learner; formation